2010
DOI: 10.1111/j.1365-2036.2010.04278.x
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of haemorrhoidal disease from a global perspective

Abstract: Summary Background  A treatment approach for patients with haemorrhoidal disease and other anal disease, which includes the use of topical corticosteroids and other topical combination products, is widely accepted, but little has been published to compare such treatments. This publication is a valuable collection of reading material for gastroenterologists, proctologists, general practitioners, dermatologists and other clinicians who are responsible for diagnosing and managing patients with haemorrhoidal disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
0
16
0
10
Order By: Relevance
“…По сути, данные симптомы -проявление воспалительного процесса в анальном канале. Это подтверждается хорошими результатами применения местной противовоспалительной терапии [6][7][8]. При этом встает вопрос о причинах возникновения воспаления в области анального канала и причинах перехода этого процесса в хроническую форму.…”
Section: зависят ли результаты лечения геморроя от строения анальногоunclassified
“…По сути, данные симптомы -проявление воспалительного процесса в анальном канале. Это подтверждается хорошими результатами применения местной противовоспалительной терапии [6][7][8]. При этом встает вопрос о причинах возникновения воспаления в области анального канала и причинах перехода этого процесса в хроническую форму.…”
Section: зависят ли результаты лечения геморроя от строения анальногоunclassified
“…Прочная связь флуокортолона с местными рецепторами определяет его крайне низкую системную биодоступность. В исследованиях было показано, что при применении ректальных свечей , содержащих 1 мг флуокортолона пивалата и 40 мг лидокаина, системная биодоступность флуокортолона пивалата составляет около 5 %, а при использовании ректального крема -около 15 % [12].…”
Section: результаты и обсуждениеunclassified
“…После местной аппликации быстро купируются боль и зуд. Действие препарата начинается уже спустя несколько минут после нанесения и продолжается примерно 1 ч [12]. Механизм действия лидокаина основан на нарушении генерации и проведения нервных импульсов путем замедления деполяризации.…”
Section: результаты и обсуждениеunclassified
“…Internal hemorrhoids become a disease when the physiological anorectal vascular cushion above the dentate-line enlarges, slides and causes anal symptoms like painless bleeding, itching and fecal soiling (1)(2)(3). An epidemiologic study from 1990 reported a prevalence rate of 4.4% for symptomatic hemorrhoids in western society (4,5).…”
Section: Introductionmentioning
confidence: 99%